2010
DOI: 10.1111/j.1742-7924.2010.00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential of sucrose‐induced analgesia to relieve pain in male adults: A preliminary study

Abstract: Aim: Sucrose-induced analgesia frequently has been investigated for pain relief during invasive procedures in neonates. This analgesic mechanism is thought to be mediated by the endogenous opioid system, taking advantage of sweet taste. However, few studies have examined the effects of sucrose-induced analgesia in adults. Therefore, this preliminary study examines the analgesic efficacy of a sucrose stimulus on experimentally induced pain in male adults. Methods: A randomized, single-masked, cross-over study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
(26 reference statements)
1
15
0
Order By: Relevance
“…[9] In the present study, 12 day ingestion of 32% sucrose solution demonstrated an analgesic effect in mice. This analgesic effect was partially inhibited by long-acting opioid receptor antagonist naltrexone (20 mg/kg), but was unmodified by the NO synthase (NOS) inhibitor L-NAME (10 mg/kg).…”
Section: Discussionsupporting
confidence: 50%
“…[9] In the present study, 12 day ingestion of 32% sucrose solution demonstrated an analgesic effect in mice. This analgesic effect was partially inhibited by long-acting opioid receptor antagonist naltrexone (20 mg/kg), but was unmodified by the NO synthase (NOS) inhibitor L-NAME (10 mg/kg).…”
Section: Discussionsupporting
confidence: 50%
“…There is evidence for a more global antinociceptive effect of certain tastants. Sucrose has been reported to elicit antinociception in juveniles (Blass et al, 1987;Miller et al, 1994;Bucher et al, 2000;Anseloni et al, 2005) and in adults (Stevens & Lawless, 1986;Kakeda, 2010;Sch€ obel et al, 2012). Water, sucrose and self-initiated ingestion of chocolate produced analgesia in rats in a manner requiring intact central antinociceptive pathways (Foo & Mason, 2009).…”
Section: Mechanisms and Functional Significance Of Tastant Modulationmentioning
confidence: 99%
“…Thus, the analgesic system block pain signals at the initial entry point to the spinal cord. 18,19 The use of different methods for evaluating pain is important because analgesic effect may be due to one or more mechanisms. For this reason in this study we have used hot plate method for supraspinal analgesia and acetic acid induced writhing for spinal analgesia.…”
Section: Discussionmentioning
confidence: 99%